Generation of EUV radiation by plasmonic field enhancement using nano‐structured bowties and funnel‐waveguides. Issue 1 (27th December 2012) - Park, In‐Yong; Choi, Joonhee; Lee, Dong‐Hyub; Han, Seunghwoi; Kim, Seungchul; Kim, Seung‐Woo; Hommelhoff, Peter; Kling, Matthias; Stockman, Mark
<x xml:space="preserve">Abstract</x> Recent experimental data of high‐order harmonic generation (HHG), obtained by use of the plasmonic field enhancement of nanostructure bowties and funnel‐waveguides, are presented. Emphasis is laid on reproduction of previous experimental results and also elucidation of the fundamental limitations associated with the nanostructure thermal damage, small laser‐gas interaction volume, and atomic line emission in the plasmon‐driven HHG process. In addition, the dominance of coherent harmonics is quantitatively verified by implementing a two‐beam interference experiment using a pair of funnel‐waveguides. This study proves that funnel‐waveguides are a superior plasmonic device capable of providing not only high thermal immunity but also sufficient atom emitters to produce practically usable extreme‐ultraviolet (EUV) radiation in a reproducible manner.